The relationship between physical activity and the incidence of dysmenorrhea among female adolescents - Maya Indria Prantini; Sunarsih Sunarsih; Annisa Ermasari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Dysmenorrhea is one of the most common reproductive health disorders experienced by female adolescents, with a global prevalence reaching 60 - 90%. In Indonesia, more than 100,000 cases have been reported. Purpose: To determine the relationship between physical activity and the incidence of dysmenorrhea among female adolescents. Method: This study employed a quantitative method with a cross-sectional design. The population consisted of all female students who experienced dysmenorrhea at SMK PGRI Palas, with a sample of 50 respondents. Data were collected using a questionnaire. Data analysis was conducted through univariate and bivariate analyses using Fisher’s Exact test to determine the relationship between variables. Results: The results showed that the majority of respondents had moderate physical activity (76%), and 60% experienced dysmenorrhea. Fisher’s Exact test indicated a significant relationship between physical activity and the incidence of dysmenorrhea (p = 0.005). Conclusion: The results of the study showed that physical activity was significantly associated with the incidence of dysmenorrhea among female adolescents.